PEMBINAAN SIKAP TAWASUTH DAN TOLERANSI PADA SISWA SMK NEGERI 3 SALATIGA - Nurul Khasanah, Ilmilia; Khasanah, Ilmilia Nurul; Zaman, Badrus (Wahana Islamika: Jurnal Studi Keislaman, 2023)
This study has two objectives, namely: 1. To describe the development of tawasuth and tolerance attitudes in students; 2. To describe the implications of fostering tawasuth and tolerance attitudes in students at SMK Negeri 3 Salatiga. This research useddescriptive qualitative research. The data sources obtained came from primary data sources, including observations and interviews with school principals, Islamic religious education teachers, and some students at SMK Negeri 3 Salatiga. Other data sources were obtained from secondary data sources through observation and photo documentation of students at SMK Negeri 3 Salatiga. The results of this study indicate, first, that fostering an attitude of tawasuth and tolerance at SMK Negeri 3 Salatiga is carried out by monitoring students, teaching, habituating to do good, participating in extracurricular activities, providing insight to add to the foundation and basis of knowledge, introducing a systematic and logical way of thinking, and receiving direct instruction from the teacher. Second, the implications of fostering an attitude of tawasuth and tolerance at SMK Negeri 3 Salatiga are cultivating an attitude of respect for others, building a sense of togetherness, forming harmony and familiarity in the school environment, having a high social spirit, being accustomed to worship, and obeying rules.